A computable general equilibrium analysis of Brexit: Barriers to trade and immigration restrictions. (25th November 2019) - Ortiz Valverde, Gabriela; Latorre, Maria C.
Abstract: This paper estimates the economic effects of different types of restrictions on trade and immigration in the United Kingdom after Brexit. Regarding trade restrictions, we focus on UK–EU increases in tariffs and non‐tariff barriers. We also analyse the removal of all tariffs in the UK to all its trading partners. Concerning immigration, we run a 5‐year cumulative annual reduction in net migrants by 87, 000 workers following OECD estimations, which looks realistic even if there is a hard Brexit. The study is conducted using a computable general equilibrium (CGE) model, which allows us to estimate the impact on GDP, welfare, wages and capital remuneration, together with the evolution of aggregate and sectoral output, exports and imports. We obtain a more sizeable negative impact on the UK than other previous influential studies. Trade restrictions would generate welfare reductions between −0.38% and −1.94% for the UK, while they would be between −0.03% and −0.14% in the EU. This is because the EU is a crucial trade partner for the UK, which cannot be easily substituted through trade with other regions in the world. We simulate the impact of both reductions in net inflows and in the stock of EU migrants, accumulated through 5 years. Migration is compatible with wage increases but puts downward pressure on GDPpc. However, migration restrictions would not compensate the overall GDPpc contractions arising from a hard Brexit.